2020
DOI: 10.1111/pin.12999
|View full text |Cite
|
Sign up to set email alerts
|

High B7‐H3 expression is linked to increased risk of prostate cancer progression

Abstract: B7-H3 is a member of the B7 superfamily of immune checkpoint molecules. B7-H3 up regulation has been linked to cancer development and progression in many tumors including prostate cancer. To clarify the potential utility of B7-H3 as a prognostic biomarker, B7-H3 expression was analyzed by immunohistochemistry in more than 17 000 prostate cancers. Normal prostatic glands were largely B7-H3 negative, while membranous B7-H3 immunostaining was seen in 47.0% of analyzed cancers. B7-H3 immunostaining was weak in 12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…B7 homolog 3 (B7‐H3) (PD‐L3, CD276) is a member of the B7 family of coregulatory molecules, 1 which also includes PD‐L1 (B7‐H1). In contrast to PD‐L1, B7‐H3 is widely expressed in prostate adenocarcinoma (PCa), and high expression has been associated with adverse pathologic features as well as a specific molecular phenotype 2‐6 . Accordingly, several previous studies have demonstrated an association between B7‐H3 expression and adverse oncologic outcomes in patients with surgically treated PCa, including early prostate‐specific antigen (PSA) recurrence 3‐5 as well as the development of castration‐resistant PCa (CRPC) and cancer‐specific death 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B7 homolog 3 (B7‐H3) (PD‐L3, CD276) is a member of the B7 family of coregulatory molecules, 1 which also includes PD‐L1 (B7‐H1). In contrast to PD‐L1, B7‐H3 is widely expressed in prostate adenocarcinoma (PCa), and high expression has been associated with adverse pathologic features as well as a specific molecular phenotype 2‐6 . Accordingly, several previous studies have demonstrated an association between B7‐H3 expression and adverse oncologic outcomes in patients with surgically treated PCa, including early prostate‐specific antigen (PSA) recurrence 3‐5 as well as the development of castration‐resistant PCa (CRPC) and cancer‐specific death 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite this progress, several unexplored areas remain as trials targeting B7‐H3 gain momentum. First, previous studies of B7‐H3 expression in PCa were conducted predominantly in European ancestry cohorts 2‐6 . Given recent evidence of differing immunobiology in prostate tumors arising in self‐identified Black (BL) patients compared with self‐identified White (WH) patients, 8‐12 we hypothesized that B7‐H3 expression may differ between races and could have a putative role in the differing immunobiology and immune therapy responses seen in these 2 groups of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, a type I transmembrane protein CD276 [ 30 ], recently identified as a promising target for tumor immunotherapy [ 31 ], is notable. Numerous studies have revealed that CD276 is overexpressed in a variety of tumors, including leukemia [ 32 ], breast cancer [ 33 ], prostate cancer [ 34 ], and other tumors, with expression levels strongly correlating with poor patient prognosis, and presumably involved in tumor immune evasion. In addition, CD276 has been shown to promote lactate production by promoting hexokinase 2 expression, thereby promoting glycolysis and drug resistance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like TIGIT, B7 homolog 3 (B7-H3), a member of the B7 family of the IgSF, is similar to PD-L1. B7-H3 is upregulated in PCa where it is negatively correlated with biochemical cancer recurrence, progression and metastasis [139]. Several studies have revealed increased B7-H3 expression that correlates with clinicopathologic indicators of aggressive cancer, metastasis and poor clinical outcomes in PCa patients [140][141][142][143].…”
Section: B7 Homolog 3 (B7-h3)mentioning
confidence: 99%